2021
DOI: 10.3390/biomedicines9101366
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Duchenne Muscular Dystrophy–Exploring the Role of Neutrophils in Muscle Damage and Regeneration

Abstract: Duchenne muscular dystrophy (DMD) is a severe and progressive, X-linked, neuromuscular disorder caused by mutations in the dystrophin gene. In DMD, the lack of functional dystrophin protein makes the muscle membrane fragile, leaving the muscle fibers prone to damage during contraction. Muscle degeneration in DMD patients is closely associated with a prolonged inflammatory response, and while this is important to stimulate regeneration, inflammation is also thought to exacerbate muscle damage. Neutrophils are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Tus, this study provides important insights into the underlying mechanisms of lncRNAs in the pathogenesis of DMD and provides potential targets that could aid in the rational design of lncRNA-based therapies for DMD. Lack of dystrophin results in chronic infammation, which is closely associated with muscle degeneration in the pathogenesis of DMD [19,20]. In our proposed DMDrelated lncRNA-mRNA pathway networks, PYCARD, RIPK2, and CASP1 were signifcantly enriched in the NODlike receptor signaling pathway, whereas MAP2K2, LUM, RPS6, PDCD4, TWIST1, and HIF1A were signifcantly enriched in proteoglycans in cancers.…”
Section: Discussionmentioning
confidence: 78%
“…Tus, this study provides important insights into the underlying mechanisms of lncRNAs in the pathogenesis of DMD and provides potential targets that could aid in the rational design of lncRNA-based therapies for DMD. Lack of dystrophin results in chronic infammation, which is closely associated with muscle degeneration in the pathogenesis of DMD [19,20]. In our proposed DMDrelated lncRNA-mRNA pathway networks, PYCARD, RIPK2, and CASP1 were signifcantly enriched in the NODlike receptor signaling pathway, whereas MAP2K2, LUM, RPS6, PDCD4, TWIST1, and HIF1A were signifcantly enriched in proteoglycans in cancers.…”
Section: Discussionmentioning
confidence: 78%
“…In particular, proinflammatory monocytes CD11b + /Ly6G − /Ly6c + have been reported to be the first innate immune cells to be mobilized from the bone marrow into the circulation and recruited to the site of tissue injury [50], such as dystrophic muscles, where they differentiated into inflammatory macrophages [51,52]. Different studies demonstrated that neutrophils actively participated in the exacerbation of muscular dystrophy and their specific depletion reduced muscular necrosis and inflammation in mdx mice [53][54][55]. Moreover, neutrophil-derived elastase impaired myoblast proliferation, survival and differentiation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanical damage and cell membrane defects are known to be basic pathological changes in DMD, the infiltration of immune cells also has a significant impact on the occurrence and progression of DMD (Tidball et al, 2018). In particular, the immune environment of the muscle tissue in DMD patients is known to restrict the therapeutic effects of some promising treatments, such as gene editing and stem cell transplantation (Duan et al, 2021;Tulangekar and Sztal, 2021). Therefore, exploring potential diagnostic biomarkers and characterizing the infiltration pattern of immune cells in DMD is of great significance to enhance the diagnosis and prognosis of DMD (Mendell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%